PENGARUH LITERASI DIGITAL TERHADAP KINERJA GURU SEKOLAH DASAR DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI: Penelitian Kuantitatif - Nurhadi, Ahmad; Tito Parta Wibowo; Asep Agus Salim; Elim Halimah Sa’diyah; Noni Nurasiah; Rista Maifi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of digital literacy on elementary school teachers’ performance with work engagement as a mediating variable. The study employed a quantitative approach using a survey design in Mandalawangi District, Pandeglang Regency. The sample consisted of 51 teachers from 7 elementary schools selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through linear regression and mediation testing with IBM SPSS Statistics version 26. The findings indicate that digital literacy has a positive and significant effect on teacher performance (β = 0.853; p < 0.05). Digital literacy also has a significant effect on work engagement (β = 0.680; p < 0.05), and work engagement significantly affects teacher performance (β = 0.392; p < 0.05). The mediation analysis shows that work engagement partially mediates the relationship between digital literacy and teacher performance. These findings contribute to the development of a teacher performance improvement model that emphasizes both digital competence and work engagement in elementary education.